Dispositifs pulsionnels et économies de la subjectivation : actualités de Nietzsche au prisme de Pierre Klossowski - Vaillancourt, Thibaut (Labyrinth, 2024)
This article aims to reposition Nietzsche's thought within contemporary fields of research through the prism of its reception by Pierre Klossowski. Our analysis makes use of Klossowski's unpublished manuscripts, allowing us to better articulate and situate Nietzsche's thought within Klossowski's thought, which is nourished by a dialogue that goes beyond his work devoted to Nietzsche and develops an analysis that is particularly amenable to updating. In developing a Nietzsche-informed general economy of subjectivation, Klossowskian theory tends toward various aspects of theoretical explorations present in media thought and the posthumanities. In doing so, we show that Nietzsche's thought, as approached by Klossowski, allows for unprecedented connections that shed light on the genealogy of the posthumanities, conceptually enrich research in Media archaeology and Science and Technology Studies, and anticipate the crucial role of affect and information in contemporary processes of subjectivation.